An analysis of capital-output ratios with special reference to South Africa - Tosti, David (School of Economics, 2016)
The purpose of this work is an analysis of the capital-output ratio in South Africa during the period 1950-1969. I will attempt to describe, on the basis of theoretical considerations, the trends in and the causes of movements of this ratio. I will attempt to relate theory (Part I and Part II) and reality (Part II). Part III will be devoted to prognostications and a comparison of foreseen data with those of the fourth E.D.P.